Peranan Mikoriza VA, Rhizobium dan Asam Humat pada Pertumbuhan dan Kadar Hara Beberapa Spesies Legum Penutup Tanah - M. Zulman Harja Utama; Sudirman Yahya (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2003)
The utilization of acid mineral soil often faces the problem of Al toxicity and low available P. The efforts to improve root function and neutralize the effect of high available Al are becoming important for increasing the growth of legumes, particularly as the cover crops at the plantation on acid soil. This research was aimed to find the effect of VA mycorrhyza inoculation, rhizobium, and humic acid on the growth and nutrient content of four different legume species. It was a three factor factorial experiment arranged in a completely randomized design with three replications. The first factor was four legume species: Calopogonium mucunoides, CaloPogonium ceurelieum, Centrosema pubescens and Puerari  iavanica the second factor was four different inoculants: none (M0), MVA (M1), rhizobium (Mz), MVA + rhizobium (M3); the third factor was two rates of humic acid application: without (Ho) and with humic acid (H1) The results proved the positive effect of those three factors on the growth of shoot and roots. The responses of root growth on microorganism inoculations and humic acid were different among the legume cover crop species. The role of humic acid was significantly better if there was a synergism between MV A and rhizobium. Key words: Mycorrhyza, Rhizobium, Humic acid, Legume cover crop